Using self-assessment to assess rural young learners’ writing skills in English foreign language classroom - Gusti Ayu Angga Ari Febriyanti; Ni Kadek Suci Laksmi Dewi; I Gusti Ayu Agung Ida Ratna Candra Dewi (English, 2018)
Authentic assessment describes the multiple forms of assessment that reflect student learning, achievement, motivation, and attitudes on instructionally relevant classroom activities. There are four forms of authentic assessment like project assessment, performance assessment, portfolio assessment and self-assessment. In this research, the researcher focus on investigate students in self-assessment. Self-assessment is a process of formative assessment during which students reflect on and evaluate the quality of their work and their learning, judge the degree to which they reflect explicitly stated goals or criteria, identify strengths and weaknesses in their work. It is also to realize the goals of students-centered learning. Self-assessment aims to help students to be independent learners. Self-assessment is considered important to the development of lifelong language learning skills and the development of more comprehensive assessment practices. One of Senior High School students from twelve grade in a rural school in Denpasar participated in this research. The research is based on the theory that metacognitive skills such as self-regulation and self-monitoring are important for the development of autonomous learning skills. Data were collected by observing them during the English class and at the end of the series of observations, and an interview session was conducted with each of them for triangulation. This research is also revealed that using self-assessment to assess young learners’ writing skills is beneficial and effective in helping them to write in the English language classroom. The value of this study is to suggest the use of a more authentic classroom assessment, particularly in English language teaching and learning.